Cheating uncovered: A deep dive into faculty and student perspectives - E. Co, Annalene Grace; Jesus, Fhrizz S. De (Edelweiss Applied Science and Technology, 2024)
The paper explored the perspectives of teacher education faculty and students on behaviors that constitute cheating. A convergent parallel mixed-methods design was used through a questionnaire that sought the respondents’ perspectives on behaviors based on five groups of given scenarios: during the test, test preparation, take-home work, research work, and laboratory report and seatwork. One hundred nineteen participants from the College of Teacher Education at a state university in region 02, Philippines, with 19 faculty and 100 students comprised the population for this study. As a result, cheating can be deliberate or accidental, done either for personal benefit or to aid a friend. Based on these and the emerging themes, the study proposes an alternative definition of cheating that is embedded in the academic setting. Any action or attempt that leads a person or group to evaluate their own or another’s performance incorrectly is considered cheating.